2021
DOI: 10.1111/nph.17146
|View full text |Cite
|
Sign up to set email alerts
|

A nonproteinaceousFusariumcell wall extract triggers receptor‐like protein‐dependent immune responses in Arabidopsis and cotton

Abstract: Summary Fusarium wilt caused by the ascomycete fungus Fusarium oxysporum is a devastating disease of many economically important crops. The mechanisms underlying plant responses to F. oxysporum infections remain largely unknown. We demonstrate here that a water‐soluble, heat‐resistant and nonproteinaceous F. oxysporum cell wall extract (FoCWE) component from multiple F. oxysporum isolates functions as a race‐nonspecific elicitor, also termed pathogen‐associated molecular pattern (PAMP). FoCWE triggers severa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 68 publications
1
7
0
Order By: Relevance
“…In one early study comparing the response of A. thaliana with the pathogenic strain Fo 5176 and the endophytic strain Fo 47, it was shown that treatment of A. thaliana seedlings with spores of Fo 47 triggers MPK3/6 activation and FRK1 expression, as was previously shown for Fo 5176 ( Babilonia et al , 2021 ). Similarly, crude cell wall extracts of both Fo 47 and Fo 5176 triggered MPK3/6 activation in A. thaliana in a CERK1/LYK5/BAK1- and SOBIR1-independent manner, indicating the presence of a cell wall-derived elicitor common to both strains that is not chitin, peptidoglycan, or unbranched β-1,3-1,4-glucan ( Babilonia et al , 2021 ). However, this elicitor still needs to be identified.…”
Section: Mamp Versus Pampsupporting
confidence: 56%
“…In one early study comparing the response of A. thaliana with the pathogenic strain Fo 5176 and the endophytic strain Fo 47, it was shown that treatment of A. thaliana seedlings with spores of Fo 47 triggers MPK3/6 activation and FRK1 expression, as was previously shown for Fo 5176 ( Babilonia et al , 2021 ). Similarly, crude cell wall extracts of both Fo 47 and Fo 5176 triggered MPK3/6 activation in A. thaliana in a CERK1/LYK5/BAK1- and SOBIR1-independent manner, indicating the presence of a cell wall-derived elicitor common to both strains that is not chitin, peptidoglycan, or unbranched β-1,3-1,4-glucan ( Babilonia et al , 2021 ). However, this elicitor still needs to be identified.…”
Section: Mamp Versus Pampsupporting
confidence: 56%
“…Many crucial genes related to VW, FW and RKN resistance were found in MQTLs regions, including four copies of GhnsLTPsA10 in MQTL-A05.1, MQTL-A10.1 and MQTL-D01.1 [ 45 ], two copies of CG02 in MQTL-A10.1 [ 46 ], GbSBT1 in MQTL-A03.1 [ 47 ], GhDHS1 in MQTL-A05.2 [ 48 ], GhPAO in MQTL-A08.1 [ 49 ], GhDSC1 in MQTL-A10.1 [ 50 ], GhPME31 in MQTL-A11.1 [ 51 ], GhMKK10 and GhSOBIR1b in MQTL-A12.2 [ 52 , 53 ], GhPGIP1 in MQTL-D01.1 [ 54 ], GhSOBIR1 in MQTL-D03.1 [ 52 ], GhHb1 and GhWAKL in MQTL-D04.2 [ 55 , 56 ], GhRLP31 in MQTL-D07.1 [ 52 ], and GhPMEI3 and GhPME2 in MQTL-D11.1 [ 51 ] (Table S4). All genes co-localized with MQTLs are related to hormone regulation, reactive oxygen species (ROS), xylem development, pathogen-associated molecular patterns (PAMP), mitogen-activated protein kinase (MAPK) cascades pathway, and synthesis of disease resistant proteins (Table S2).…”
Section: Resultsmentioning
confidence: 99%
“…As for MQTL-D11.1, pectin methylesterase-inhibiting protein GhPMEI3 interacts with pectin methylesterases (PMEs) and regulates the expression of a fungal specific polygalacturonase (VdPG1), plays a role in cotton responses to infection by the fungus V. dahliae [ 51 ]. GhSOBIR1 , which co-located with MQTL-D03.1, activates the plant resistance pathway by participating in pathogen-associated molecular pattern (PAMP) signaling [ 52 ]. These results confirm that the MQTLs region contained key genes involved in response to disease and can be used as candidate regions for map-based cloning of disease resistance genes.…”
Section: Discussionmentioning
confidence: 99%
“…BAK1 is required for VdEG1 and VdEG3-triggered immunity, while SOBIR1 is specifically required for VdEG1-triggered immunity in N. benthamiana (Gui et al, 2017). In the process of screening potential recognition receptors of F. oxysporum cell wall extract (FoCWE), two receptor-like proteins (GhRLP20 and GhRLP31) in cotton were found to be required for the recognition of FoCWE and Fusarium resistance (Babilonia et al, 2021). SRE1-induced plant cell death was independent of BAK1 and SOBIR1 in this study (Figure 4).…”
Section: Discussionmentioning
confidence: 99%